A natureza do ser: visão espírita - Carvalho, Edilmo Vieira de (2011)
Throughout history the analysis about the Nature of Being has been conducted between the soul (or spirit), to be immaterial, and the resulting awareness of the matter. Greeks in antiquity to modern times the debate has been made between philosophical idealism and philosophical materialism. From the nineteenth century is to have a contribution to the study of Spiritism. The purpose of this research was to examine the nature of being from the perspective of philosophers supporters of philosophical idealism, philosophical materialism and Spiritism. The methodological procedures adopted in the research, considering it is qualitative, exploratory and bibliographic aimed at identifying the relationship between spirit and matter, while the nature of being, in view of Spiritism. According to Spiritism the universe has an intelligent planning, where all resources are worked in co-creation of tiny beings, early in its evolution, to the angelic potencies to the Supreme Lord. The Spirit is the holder of intelligence, matter is only an instrument.